No Balm (in) Gilead: Aspects of Cultural Communication in Stephen King’s “The Dark Tower” Book Series - Bojan Žikić (University of Belgrade, 2020)
Three aspects of cultural communication of Stephen King's “The Dark Tower” book series are discussed in this paper: a literary tradition, a literary genre, and a cultural message. Narrative motives are established as a mean of connection of this book series with some of the classic works of English and European literature, and the whole series is fashioned according to the literary form of the (folk or fairy) tale. The purpose of this is to refer to the idea that a given book series should be viewed as part of English literature and of the English literary tradition. The tale form is used as a mean of categorizing the literary form within a given literary tradition. The third aspect in which the series communicates is the social context in which it was created, and it establishes parallels between states of social stability and instability, order and chaos, wholeness and breakup in the two basic worlds in which the series' action takes place: in our world and in that of the principle protagonist. It aims to emphasize the responsibility of the individual for the functioning of society, since society represents a consensual community of individuals.